Tumor budding correlates with tumor invasiveness and predicts worse survival in pT1 non-muscle-invasive bladder cancer - Eckstein, Markus; Kimmel, Charlotte; Bruendl, Johannes; Weber, Florian; Denzinger, Stefan; Gierth, Michael; Burger, Maximilian; Hartmann, Arndt; Otto, Wolfgang; Breyer, Johannes (Scientific Reports, 2021)
Tumor budding is defined as a single cell or a cluster of up to 5 tumor cells at the invasion front. Due to the difficulty of identifying patients at high risk for pT1 non-muscle-invasive bladder cancer (NMIBC) and the difficulties in T1 substaging, tumor budding was evaluated as a potential alternative and prognostic parameter in these patients. Tumor budding as well as growth pattern, invasion pattern and lamina propria infiltration were retrospectively evaluated in transurethral resection of the bladder (TURB) specimens from 92 patients with stage pT1 NMIBC. The presence of tumor budding correlated with multifocal tumors (p = 0.003), discontinuous invasion pattern (p = 0.039), discohesive growth pattern (p < 0.001) and extensive lamina propria invasion (p < 0.001). In Kaplan–Meier analysis, tumor budding was associated with significantly worse RFS (p = 0.005), PFS (p = 0.017) and CSS (p = 0.002). In patients who received BCG instillation therapy (n = 65), the absence of tumor budding was associated with improved RFS (p = 0.012), PFS (p = 0.011) and CSS (p = 0.022), with none of the patients suffering from progression or dying from the disease. Tumor budding is associated with a more aggressive and invasive stage of pT1 NMIBC and a worse outcome. This easy-to-assess parameter could help stratify patients into BCG therapy or early cystectomy treatment groups.
CRIS-Team Scopus Importer:2021-09-17